Designing Independent Automatic Drinking Water Platforms At Universitas Sanata Dharma - Sulistyanto, Muhammad Prayadi; Pramesta, Ervan Erry (International Journal of Applied Sciences and Smart Technologies, 2019)
Environmental pollution is increasing every year. From 2011 to 2014, environmental pollution in the Special Region of Yogyakarta increased above 250 percent. The effect of environmental pollution is the decreasing availability of clean water. Universitas Sanata Dharma as an institution engaged in the field of Education seeks to provide clean water where clean water is suitable for drinking, namely with RO (Reverse Osmosis) technology. Drinking water distribution has run well in the Universitas Sanata Dharma, but it lacks hygiene. In this study, researchers Designing Independent Automatic Drinking Water Platforms that could distribute clean water ready to drink students with a certain dose. The result of this study is that an independent automatic drinking water platform can provide 200cc of clean water ready for drinking in 9 seconds each time a user (student) uses this tool.